P571 Effectiveness and safety of Ustekinumab for induction of remission in patients with Crohn's disease: a multi-centre Israeli study. (25th January 2019) - Bar-Gil Shitrit, A; Siterman, M; Waterman, M; Hirsh, A; Khoury, T; Schwartz, D; Zittan, E; Adler, J; Koslowsky, B; Avni-Biron, I; Chowers, Y; Ron, Y; et al.
Abstract: Background: Background: Ustekinumab was demonstrated to be effective in treatment of Crohn`s disease in UNITI studies that used intravenous induction followed by subcutaneous maintenance. Several real-world evidence (RWE) studies addressing the efficacy of ustekinumab given subcutaneously were published. However, RWE data regarding effectiveness of the currently approved ustekinumab regimen are lacking. Our aim was to assess the safety and efficacy profile of ustekinumab for induction of remission in a large national patient cohort. Methods: A prospective multi-centre study was conducted. Patients with active Crohn`s disease (CD) that were treated with ustekinumab were followed for 24 weeks. Patients who completed the induction protocol (week 0/8/16) or discontinued the treatment before Week 24 for adverse events or primary non-responders, were included. Induction dose was 260 to 520 mg (intravenous) according to body weight and then 90 mg subcutaneously every 8 weeks. Primary end-points were clinical response (reduction of ≥3 points in Harvey–Bradshaw score) and corticosteroid-free clinical remission at Week 24. Results: A total of 106 CD patients from 8 Israeli medical centres were included. Median age was 38 years (range 21–74) with median disease duration of 13 years; 64 (60%) were female patients. Eighty-five (80%) previously experienced at least two prior biological agents (anti-TNFs and vedolizumab) and only 1 patient (0.94%) was anti TNF naïve. Sixteen patients (15%) were after ileo-colic resection. Out of 106 patients, 10 (9.4%) patients discontinued treatment due to non-response and 4 (3.7%) due to adverse events, mostly worsening of arthralgia. Ninety-one patients continued treatment through Week 24. Clinical response was observed in 38 patients (36%). Ustekinumab induced significant decrease in mean CRP levels ( p < 0.004). Twenty-one patients out of 32 (66%) achieved steroids-free remission at Week 24. Extra-intestinal manifestations (EIMs) at baseline included articular involvement in 32 patients (30%), skin manifestations in 8 patients (7.5%), biliary in 1(0.1%) and ocular in 1 patient (0.1%). Improvement of most probably arthralgia was observed at Week 24 in 23/32 patients (71%). Twenty-four patients (23%) reported of active perianal disease at the beginning of the study and 5(20%) of them improved at Week 24. Adverse events were reported in 12 (11%) patients, most common being arthralgia, weakness and skin eruptions. Conclusions: In a large real-world Israeli cohort of anti-TNF- experienced CD patients, ustekinumab was effective and safe in induction of clinical remission and steroid-free clinical remission.